Model of effective and efficient village fund management policy in Indonesia - Taufik Madjid; Sadu Waisitiono; Tjahya Supriatna; Hadi Prabowo (Interdisciplinary Social Studies, 2024)
The Village Fund is a strategic policy to promote equitable rural development and empower local communities in Indonesia. However, despite notable effectiveness—reflected in high fund absorption, improved village status, reduced unemployment, and increased income—its implementation faces significant efficiency challenges due to overlapping regulations, fragmented authority, and poor institutional coordination. This study aims to analyze the factors affecting the effectiveness and efficiency of Village Fund management and to formulate a comprehensive policy model. Using a qualitative descriptive approach, data were collected through literature review, interviews, focus group discussions, and field observations, followed by coding analysis. The findings reveal that macro-level issues such as regulatory dualism and institutional conflicts cascade into micro-level inefficiencies, including the neglect of community empowerment and underutilized village institutions. To address these challenges, the study proposes a conceptual model that integrates the four formal objects of government science—authority, institutional relations, public services, and welfare—with the "one-door" policy approach. This model advocates for centralizing Village Fund authority under one coordinating ministry supported by others, thereby streamlining structure, enhancing public service efficiency, and improving community welfare. The study also emphasizes transparency, responsiveness, technological integration, and inclusive participation as critical components. The implications suggest that while the model offers structural clarity and governance innovation, further empirical research using positivist methods is required to validate and operationalize its impact in practice.